PERBEDAAN KEMAMPUAN TANAH DALAM MENAHAN AIR PADA BERBAGAI KELERENGAN LAHAN KOPI DI DAERAH SUMBERMANJING WETAN, KABUPATEN MALANG - Awal Maulana Faiz; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Water is a natural resource that is very important because its existence is needed for living things, including plants that need water for their growth and development. The availability of water in the soil has different amounts because it is influenced by various soil properties in the land. Land that has a sloping ground surface, the movement of water that enters the ground does not only move vertically as in land that has a flat surface but also laterally is parallel to the sloping land surface and moves down the slope. The first land has a slope percentage of 6%, the second has a slope of 13%, the third has a slope of 23%, and the fourth has a slope of 37%. The study consisted of 4 treatments for different levels of a land slope, and nine replication points were carried out. The results of this study indicated that the difference in the level of slope in each land had an effect on the water content in the soil at a depth of 40-60 cm; the higher the percentage of the slope of the land reduced the availability of groundwater. Specific gravity, porosity, and soil meso pore had a significant effect on the soil water content with a positive correlation direction, meaning that the higher the density, porosity, and soil meso pores, the more water available in the soil. Macro pores and soil micro pores had a significant effect on soil water content with a negative correlation, meaning that the higher the macro pores and soil micro pores will reduce the available water in the soil.